2017
DOI: 10.26466/opus.370680
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmenlerin Lisansüstü Eğitim Yapmama Nedenlerinin İncelenmesi

Abstract: Öz

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 2 publications
0
2
0
3
Order By: Relevance
“…Based on the teachers' views, it is concluded that graduate education and in-service trainings are important for teachers to keep up with scientific developments and keep their knowledge up-to-date. This view is also supported by Şişman (2002), Akpınar (2012), and Toprak and Taşğın, 2017. This implies that encouragement of teachers to enroll graduate schools in order to increase their professionalism as well as the effectiveness of schools.…”
Section: Discussionmentioning
confidence: 87%
“…Based on the teachers' views, it is concluded that graduate education and in-service trainings are important for teachers to keep up with scientific developments and keep their knowledge up-to-date. This view is also supported by Şişman (2002), Akpınar (2012), and Toprak and Taşğın, 2017. This implies that encouragement of teachers to enroll graduate schools in order to increase their professionalism as well as the effectiveness of schools.…”
Section: Discussionmentioning
confidence: 87%
“…In a similar vein, metaphors like climbing the stairs by five stairs each time, a path full of obstacles, an onion, the final boss of the game, a marathon, fitness, and solving puzzles were categorized under the theme of the challenge. Likewise, Toprak and Taşğın (2017) found that a master's degree demands a long-lasting and challenging education. These arguments indicated that participants' negative thoughts about a master's degree affected their willingness/unwillingness to have this education and their metaphorical understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Nitekim öğretmenlerin profesyonel gelişimleri için aktif okul liderliği ve iyi yapılandırılmış öğrenme kültürünün okullarda benimsenmesi gerekmektedir (Desimone, 2009). Öğretmenlere göre, lisansüstü eğitim yoğun ve yıpratıcı bir süreçtir (Toprak ve Taşğın, 2017) ve öğretmenlik mesleği ile lisansüstü eğitimi birlikte yürütmenin ekonomik ve psikolojik açıdan çeşitli zorlukları bulunmaktadır (Balıkçı vd., 2018;Leonard vd., 2005).MEB'in eğitim yapılan yere atama yapmaması (Başer vd., 2005;Karakütük, 2000;Nayır, 2011), yöneticilerin öğretmenlerin lisansüstü eğitime devam etmesine izin verme konusunda isteksiz davranması, kolaylaştırıcı olmaması (Sever ve Ersoy, 2019) bu sorunlar arasında sayılabilir. Bu sorunların çözümüne yönelik atılacak adımlar, öğretmenlerin lisansüstü eğitimi "öğretmenliği bırakmak için (akademiye geçiş)" değil, öğretmenliğe güçlü biçimde devam etmek için yapmalarını sağlayabilir.…”
Section: Lisansüstü Eğitim Alma Nedenleriunclassified